2006
DOI: 10.1590/s1806-37132006000400012
|View full text |Cite
|
Sign up to set email alerts
|

Coexistência de transtornos respiratórios do sono e síndrome fibromiálgica

Abstract: Objective: To identify fibromyalgia syndrome in patients with sleep disordered breathing. Method: We studied 50 patients seeking treatment at a sleep disorder clinic for snoring, apnea and excessive daytime sleepiness. Sleep disordered breathing was diagnosed through the use of polysomnography. To diagnose fibromyalgia syndrome, patients were evaluated in accordance with the criteria established by the American College of Rheumatology. Results: Of the 50 patients, 32 were male. The mean (± standard deviation) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…That decision seemed appropriate because, in contrast to early studies that suggested a high rate of sleep disorders in CFS [ 6 - 8 ], later studies including our own found no difference in rates of sleep disorders between patients with CFS and healthy controls [ 9 - 11 ]. In contrast, except for our own work [ 11 ] and one other early study [ 12 ], a number of other studies suggests that FM is often accompanied by sleep-disordered breathing (SDB) [ 13 - 16 ].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…That decision seemed appropriate because, in contrast to early studies that suggested a high rate of sleep disorders in CFS [ 6 - 8 ], later studies including our own found no difference in rates of sleep disorders between patients with CFS and healthy controls [ 9 - 11 ]. In contrast, except for our own work [ 11 ] and one other early study [ 12 ], a number of other studies suggests that FM is often accompanied by sleep-disordered breathing (SDB) [ 13 - 16 ].…”
Section: Introductionmentioning
confidence: 74%
“…Two small studies used the approach we had taken here of evaluating patients with PSG-proven SDB for FM. One study found no increase in FM in SDB [ 12 ] while the second did [ 16 ]. We expect these discrepancies may be due to methodological differences related to our excluding patients with multiple sleep diagnoses and/or issues related to sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, there is conflicting literature demonstrating whether or not adults with sleep apnea have an increased incidence FMS [92–94]. Previous research demonstrates that children with JFMS have altered alpha-delta sleep but that this sleep abnormality does not correlate with chronic pain or subjective sleep quality [95].…”
Section: Non-pharmacological Managementmentioning
confidence: 99%
“…Interestingly, elevated body mass index, blood pressure, and waist-to-hip ratio are associated with sleep-disordered breathing. We recently reported in a study that 50% of the women with obstructive sleep apnea syndrome or upper airway resistance syndrome had chronic pain and more than 11 tender points when pressed with 4 kgf/cm 2 [ 7 ]. Guille-minault and colleagues [ 8 ] reported orthostatic intolerance in patients with upper airway resistance syndrome.…”
mentioning
confidence: 99%